Comparação da resposta tribológica de duas configurações do par anel de óleo e camisa de cilindro de motores diesel - Salsamendi, Sergio (2020)
The current work aims to evaluate the tribological behavior of two ‘ring TLOCR – liner’ systems, varying the geometry of contact area of the TLOCR rings (twin land oil control ring), in addition to the normal contact force and the liner roughness. For this evaluation liners samples were used, manufactured in gray cast iron, with small variations of roughness (characterized in an optical interferometer) and two concepts of control rings, called V-shape, in nitrided steel and normal force of 28 N, and X-taper, in cast iron with chrome plating and normal strength of 86 N. The interfacial element used for both tests was the semi-synthetic oil ALFAP PAO (SAE 10W30- API CK-4), with a kinematic viscosity rated at 100 ° C from 9.3 to 12.5 mm² / s (cSt), always new for each test. A universal tribometer with a reciprocating module was used, with loads of 28 or 86 N and oil temperature kept constant at 90 ° C. The tribological tests were carried out for two hours and their results were analyzed in 6 segments (”leg” 1 to 6) of 20 minutes each, for each repetition. Six repetitions were made for each system. Each liner sample was again evaluated on an optical interferometer to determine wear, comparing the roughness parameters of the Abbott curve before and after each test. A ferrography oil analysis was performed for each system. The analysis of the lubrication regime showed that all tests were carried out within the mixed region. As a conclusion, it was observed that the mean values of friction coefficient were significantly similar for the two systems, as well as the differences in wear, assessed by means of topographic variation, but sufficient to differentiate the systems.